Assessing Feed Color Preference of Broilers During the Starter Phase - Jose I. Vargas; Abigail D. McConnell; Joseph P. Gulizia; Wilmer J. Pacheco; Kevin M. Downs (Poultry)
Chickens possess a well-developed vision that allows them to perceive a wide range of the color spectrum. In addition, they display an inherent sensitivity toward specific light spectra, which suggests that coloring feed could influence feed preference, feed intake and growth performance. This trial assessed the effect of feed coloring on broiler feed color preferences. A total of 216 day-old Cobb by-product males were randomly distributed into 18 battery cages, each containing 12 chicks and subjected to three dietary treatments from 1 to 21 days, resulting in six replicates per dietary treatment. Feed color treatments consisted of a common corn–soybean meal-based undyed basal (UB) broiler starter diet, which was dyed to obtain blue-colored (B) and purple-colored (P) diets, resulting in a total of three diets used to create the feed combinations. Two feed troughs were affixed to each cage, allowing for the assignment of dietary treatments as follows: UB-B, UB-P, and B-P. The birds had ad libitum access to feed and water throughout the study. Feed consumption data were collected at 7-day intervals. Additionally, bird weights were measured at 1 and 21 days. The data were analyzed as a completely randomized design using the SAS GLIMMIX and TTEST procedures. Overall, broilers exhibited a preference for the UB diet compared to the B and P diets. Broilers had a 27.5 and 29.2% higher (p < 0.05) feed consumption of UB feed compared to P feed from 1 to 14 and 1 to 21 days, respectively. In addition, broilers tended to have a higher (p = 0.098) consumption of UB feed compared to B feed from 1 to 14 days. No differences were observed in feed consumption between B and P diets during the experimental period. Based on feed consumption data, broilers displayed a preference towards the UB feed when paired with B or P diets. Feed coloring did not impact the mortality of broilers and did not result in adverse growth. Overall, broilers preferred the UB diet over the B and P diets and showed no preference between B and P diets. Based on the results of this trial, diets that appear more conventional, compared to dyed diets, can promote consumption. Special care must be taken to avoid ingredients that could alter the diet’s coloration.